High-Sensitivity C-Reactive Protein: An Independent Risk Factor for Left Ventricular Hypertrophy in Patients with Lupus Nephritis. (17th October 2010) - Shi, Beili; Ni, Zhaohui; Cai, Hong; Zhang, Minfang; Mou, Shan; Wang, Qin; Cao, Liou; Yu, Zanzhe; Yan, Yucheng; Qian, Jiaqi
Abstract : Objective . To determine the prevalence of left ventricular hypertrophy (LVH) and its associated risk factors in lupus nephritis (LN) patients. Methods . 287 LN patients (age: 38.54± 13.31, 262 female) were recruited. Echocardiography and serum high-sensitivity C-reactive protein (hs-CRP) were measured. Their relationship was evaluated by univariate correlation analysis and multivariate regression analysis. Results . The prevalence of LVH in this cohort was 21.25% (n = 61 ). Serum hs-CRP level was significantly elevated in patients with LVH compared to those without (8.03 (3.22–30.95) versus 3.93 (1.48–9.48) mg/L, P < .01), and correlated with left ventricular mass index (LVMI) (r = 0.314, P = .001 ). Multivariate regression analysis further confirmed that hs-CRP was an independent risk factor (β = 0.338, P = .002 ) for LVH in patients with LN. Conclusions . Our findings demonstrated that serum hs-CRP level is independently correlated with LVMI and suggested that measurement of hs-CRP may provide important clinical information to investigate LVH in LN patients.